The prevalence of non-contact muscle injuries of the lower limb in professional soccer players who perform Salah regularly: a retrospective cohort study - Bezuglov, Eduard (J Orthop Surg Res, 2020)
BACKGROUND: The present study assessed the prevalence of non-contact muscle injuries of the lower limbs, including hamstring injuries, in professional Russian soccer players who regularly perform Salah, an obligatory Muslim prayer performed 5 times a day. METHODS: Using a retrospective cohort study design, 68 professional male soccer players (excluding goalkeepers), 34 of whom were Muslims regularly performing Salah (exposure group) and 34 were randomly chosen non-Muslim players (control group), were included in the study. The groups were similar in their playing leagues, field positions, age (27 ± 3.1 vs 28 ± 4.2 years), and body mass index (22 ± 1.2 vs 23 ± 0.92 kg/m(2)). RESULTS: The incidence of hamstring injury was significantly lower in the exposure group (2 vs 14, p = 0.0085). A declining trend for the number of muscle injuries (either hamstring or not) was observed in the exposure group (11 vs 27, p = 0.0562). Two players in the exposure group and 11 in the control group (p = 0.0115, OR 0.1307, 95% CI 0.0276 to 0.5698) suffered a hamstring injury, with no statistically significant difference in the occurrence of other injuries. The total amount of the training and play days missed because of hamstring and other muscle injuries was significantly lower in the exposure group (24 vs 213 days, p = 0.0043, and 200 vs 344 days, p = 0.0066, respectively). CONCLUSION: The prevalence of non-contact muscle injuries, including hamstring injuries, was lower in professional Russian soccer players who regularly performed Salah.